Ascites Due To Pseudomyxoma Peritonei (Pmp): A Rare Case Report - Ferdinal Ferry; Puti Fajri Lestari; Syamel Muhammad (Fakultas Kedokteran Universitas Andalas, 2026)
Introduction: Pseudomyxoma Peritonei (PMP), also known as